minat siswa Survei Minat Siswa Dalam Mengikuti Pembelajaran Pendidikan Jasmani Pada Materi Bola Basket Di SMP Negeri 1 Tirtamulya: Survey of Student Interest in Taking Physical Education Learning on Basketball at SMP Negeri 1 Tirtamulya - SITI DAINAH DAIN; Rahmat Iqbal; Rizki Aminudin (Universitas Singaperbangsa Karawang, 2022)
In this study, the purpose of this study was to determine student interest in participating in physical education learning on basketball material at SMP Negeri 1 Tirtamulya. In this study using a quantitative approach, using a survey method. The population in the study was all students of class VIII SMP Negeri 1 Tirtamulya, Karawang district, which found 435 students while the sample was using total sampling technique. The sample in this study was 108 students who were given a student interest questionnaire sheet. Then the data was processed using the help of Microsoft Excel 2013. In the results of the study showed that students' interest in physical education in basketball material at SMP Negeri 1 Tirtamulya showed a percentage of 34% or 37 students in the medium category